The Role of Artificial Intelligence in Enhancing Human Potential: A Comparative Analysis of Global Practices and the Case of Uzbekistan - Holmirzaev Hurshid Nakibillayevich (Periodica Journal, 2025)
The Role of Artificial Intelligence in Enhancing Human Potential Artificial Intelligence (AI) has emerged as a transformative force in the 21st century, reshaping the boundaries of human capabilities and societal structures. This study examines the role of AI in enhancing human potential through intellectual, creative, and socio-economic dimensions. Drawing on a comparative analysis of global practices and the current state in Uzbekistan, the paper highlights the mechanisms by which AI fosters innovation, optimizes decision-making, and augments human productivity. Methodologically, the research integrates theoretical frameworks with case studies from the United States, the European Union, Japan, South Korea, and China, alongside an assessment of national initiatives. Findings reveal that AI serves not only as a technological tool but also as a catalyst for rethinking education, healthcare, and professional competencies. However, the paper also identifies challenges, including ethical considerations, socio-economic inequality, and the risk of skill obsolescence. Recommendations focus on strategic policy measures, interdisciplinary collaboration, and targeted educational reforms to ensure that AI contributes equitably to human development
Keywords: Artificial Intelligence; Human Potential; Creativity